Implications of microRNAs in Colorectal Cancer Development, Diagnosis, Prognosis, and Therapeutics - Zhai, Haiyan; Ju, Jingfang (Frontiers in Genetics, 2011)
MicroRNAs (miRNAs) are a class of non-coding small RNAs with critical regulatory functions as post-transcriptional regulators. Due to the fundamental importance and broad impact of miRNAs on multiple genes and pathways, dysregulated miRNAs have been associated with human diseases, including cancer. Colorectal cancer (CRC) is among the most deadly diseases, and miRNAs offer a new frontier for target discovery and novel biomarkers for both diagnosis and prognosis. In this review, we summarize the recent advancement of miRNA research in CRC, in particular, the roles of miRNAs in colorectal cancer stem cells, EMT, chemoresistance, therapeutics, diagnosis and prognosis.